Effect of Captopril on Gentamicin Induced Nephrotoxicity in Rats - Rahman, MH; Hossain, MZ; Rahman, MA; Khan, MI (Journal of Dhaka Medical College, 2010)
The present study was performed to investigate the nephroprotective effects of captopril in experimentally induced nephrotoxicity in rats. To demonstrate this effect, serum level of creatinine and blood urea nitrogen(BUN) was chosen. Histological examination of kidney was also performed. For the purpose of the study 35 long Ivan rats were taken divided into five groups(G-A,G-B,G-C,G-D and G-E)comprising 7 rats each. Group A received .75ml distilled water subcutaneously in addition to normal diet, and served as control . Group B was treated with gentamicin 125mg/kg subcutaneously for 9 days and served as experimental group. Group C,D and E were designed to demonstrate the nephroprotective effect. In this part of experiment, group C was treated with only gentamicin 125mg/kg subcutaneously for 9 days and served as control. Group D and group E were treated with captopril 9mg/kg and 11mg/kg orally respectively, in addition to gentamicin. Mean serum creatinine and BUN level raised highly significantly in group B in comparison to group A after 9 days treatment with gentamicin. Histological findings showed a number of necrosed proximal convoluted tubules in group B whereas normal architecture is preserved in group A. Co administration of captopril prevented significantly gentamicin induced increase serum creatinine and BUN. Though histological findings did not correlate with biochemical findings and there are significant numbers of necrosed proximal convoluted tubules. From the result and observations of the present study and their comparison with the works of other researchers, it may be concluded that captopril is beneficial in protecting gentamicin induced nephropathy. Thus, it could be useful in nephrotoxic conditions, such as hypertension with acute glomerulonephritis, acute renal failure and chronic renal failure. But before establishing captopril as a therapeutically effective nephroprotective agent further studies should be carried out to determine the nephroprotective effect and its cellular mechanism as well as any clinical trial for suitability of using in man. Key Words: Captopril; Gentamicin Induced Nephrotoxicity. DOI: 10.3329/jdmc.v18i1.6297 J Dhaka Med Coll. 2009; 18(1) : 3-7